Pengaruh Brainstorming Dan Fraud Risk Terhadap Deteksi Potensi Kecurangan Oleh Auditor - Dien Auwaliah Latuconsina; Syamsuri Rahim (AkMen JURNAL ILMIAH, 2021)
The aim of this research is to analyse the influence of brainstorming and fraud risk on detection of fraudulent potential by auditors. The hypotheses are about brainstorming and fraud risk has a significant impact on detection of fraudulent potential by auditors. The data required in this research is primary data in the form of respondent’s assessment of brainstorming, fraud risk and detection of fraudulent potential by auditors. This research was carried out on Badan Pengawasan Keuangan dan Pembangunan (BPKP) of South Sulawesi Province by distributing questionnaires to 57 auditors as the respondent however only 34 questionnaires can be processed. Data analysis techniques used by determination test, F test, Multiple Linear Regression test, and t test. The results of the data analysis showed that the brainstorming and fraud risk have a significant influence on detection of fraudulent potential by auditors BPKP South Sulawesi Province either partially or simultaneously.